STUDY OF STUDENTS' CONSUMPTION BEHAVIOR IN THE PURCHASE OF FASHION PRODUCTS IN THE CITY OF PALANGKA RAYA ISLAMIC ECONOMIC PERSPECTIVE - Akbar, Wahyu; Tarantang, Jefry; Sa'diah, Maulida (Lembaga Pengembangan Kinerja Dosen, 2022)
Consumer behavior in accordance with the provisions of the Qur'an and As-Sunnah will certainly lead to goodness, blessing and maslahah. The needs of every human being are not just to eat and drink, but also in terms of appearance. So based on this to find out more about how consumer behavior towards the purchase of fashion products. This study aims to determine the consumer behavior towards the purchase of fashion products on students. Then the consumption behavior of purchasing fashion products for IAIN Palangka Raya students and UPR students is viewed from the perspective of Islamic economics. This research is a field research using a qualitative approach and analyzed holistically. The subjects in this study were students consisting of 10 IAIN Palangka Raya students and 10 UPR students. Data collection techniques by observation, interviews and documentation. The results showed that of the students of IAIN Palangka Raya and UPR, there were 5 people who were extravagant because they always followed their passions and sought pleasure while the other 15 were frugal because they knew the limits of consumption and had also been accustomed from a young age not to be extravagant in their consumption. use property. Of the two differences are influenced by personality factors as well as social factors. An overview of Islamic economics on consumption behavior is that it does not apply extravagantly and excessively and does not apply dzalim, because Islamic economics has the main goal of seeking maslahah to achieve success and prosperity in life in this world and the hereafter.